2018
DOI: 10.32598/sija.13.2.250
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Effect of Rosa Damascena Juice Aromatherapy on Elderly Chronic Musculoskeletal Pain in Sabzevar Retirement Clubs

Abstract: Objectives Chronic pain is one of the major health issues during older age. Aromatherapy is a method to reduce such pain. The present study investigated the effects of inhaling rose extract on chronic musculoskeletal pain in elderly. Methods & Materials The clinical trial consisted of 60 elderly individuals with chronic musculoskeletal pain, who were members of the retirement centers of Sabzevar city in 1395. The subjects were randomly allocated to two groups: intervention (31 people) and control (29 people). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results of one study showed that inhaling rose extract on the emotional and emotional dimension of pain in women and men was not effective. Meanwhile, the inhalation of R. damascena extract on the sensory dimension was significantly different between men and women, but the emotional dimension was not different between women and men (36).…”
Section: Rosa Damascena Millmentioning
confidence: 77%
“…The results of one study showed that inhaling rose extract on the emotional and emotional dimension of pain in women and men was not effective. Meanwhile, the inhalation of R. damascena extract on the sensory dimension was significantly different between men and women, but the emotional dimension was not different between women and men (36).…”
Section: Rosa Damascena Millmentioning
confidence: 77%
“…The McGill questionnaire measures pain perception in four dimensions: sensory, emotional, pain assessment, and various pains, and the overall pain intensity can be calculated by summing the scores of the four dimensions. This questionnaire has a Cronbach's alpha coefficient of 0.94, and its validity in all the domains is more than 0.91 (25).…”
Section: Methodsmentioning
confidence: 99%